Numerical investigation on effects of side curtain opening behavior on indoor climate of naturally ventilated dairy buildings - Li, Qifeng; Yao, Chunxia; Ding, Luyu; Yu, Ligen; Ma, Weihong; Gao, Ronghua; Zheng, Wengang (International Journal of Agricultural and Biological Engineering, 2020)
The side-curtain is popular in cattle buildings to regulate indoor climates and ventilation rates by adjusting the opening ratio. It normally had three different adjusting strategies relate to the position of rollers, i.e. central roller (S1), top roller (S2) and bottom roller (S3), which result in different opening behaviors to generate the same opening ratio but different opening positions in the side wall for a full-curtain house. Numerical simulations were conducted using computational fluid dynamics (CFD) to investigate the effects of the eight potential opening behaviors of side curtains on the indoor climates and airflow rates in winter for a typical naturally ventilated dairy house in China when the opening ratio were 8.5% and 17%. Airflow patterns, wind chilled temperature (WCT) and age of air were analyzed in the animal occupied zone (AOZ) by taking reference planes. Openings at the very bottom of side walls had more efficient ventilation due to the younger air age, more effective air disturbing, more uniformly distributed indicators in AOZ. However, it will result in a lower WCT in AOZ although a lower ventilation rate was observed in this case. Openings on the very top of side wall would generate a better thermal comfort in AOZ but with very poor air quality and nonuniformly distributed airflows in the dairy house. S1 was not recommended to the practical application due to the poor indoor climate and the higher cost of the mechanical structure. Based on the comprehensive evaluations of the analytic hierarchy process, the most satisfaction opening positions were at the bottom of the side curtains and the optimized adjusting strategy is S2. Keywords: thermal comfort, age of air, ventilation rate, computational fluid dynamics, analytic hierarchy process DOI: 10.25165/j.ijabe.20201305.5805 Citation: Li Q F, Yao C X, Ding L Y, Yu L G, Ma W H, Gao R H, et al. Numerical investigation on effects of side curtain opening behavior on indoor climate of naturally ventilated dairy buildings. Int J Agric & Biol Eng, 2020; 13(5): 63–72.